MAKNA PERSAHABATAN DENGAN KAUM NASRANI DALAM SURAT AL-BAQARAH AYAT 120 DAN AL-MAIDAH AYAT 82 - Nasution, Alhafidh; Mawardi, Mawardi (LPPM Institut Daarul Qur'an Jakarta, Indonesia, 2021)
Christians and Jews are likely similar in responding to Islam and its development. It can be seen from their unwillingness in accepting the truth of Islam which is completed by the prophet Muhammad. Their rejection do not specifically represent Christians and Jews as a whole because there are some Christians that have a good relationship with moslems. Using library research technique, main sources come from commentary and history books. The result of this research indicates that King Najasyi along with its Christian society have a close relationship with moslems. When moslems are intimidated and oppressed by infidels of Mecca, King Najasyi gladly accepts their coming and treats them well in Habasyah.